Short-Term Changes in Weight-Related Anthropometric Indicators After Locally Based Supplementary Feeding Among Stunted Children - Karjono, M.; Murtiananingsih, Murtiananingsih; Zaidah, Una; Rakhmawati, Baiq Fathin Ayu; Mulianingsih, Misroh; Fajriani, Shindy; Gonçalves, Marilia Juvi (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2026)
This study examined short-term anthropometric changes associated with locally based supplementary feeding among stunted children aged 6–59 months at Meninting Health Center, West Lombok. The feeding package consisted of mung bean porridge (100 g), egg biscuits (50 g), and sweet potato bars (50 g), providing approximately 350–450 kcal and 12–16 g protein per child per day. Using a one-group pretest-posttest design, 50 stunted children underwent anthropometric assessment at baseline, week 4, and week 8, with weekly monitoring of body weight and body height. Primary outcomes were weight, height, weight-for-age z-score (WAZ), height-for-age z-score (HAZ), and weight-for-height z-score (WHZ). Adherence was high, with 90.0% of participants consuming at least 80% of the planned feeding days. Body weight increased significantly at week 4 (mean difference = 0.15 kg, 95% CI [0.10, 0.20], p < .001) and week 8 (mean difference = 0.48 kg, 95% CI [0.39, 0.56], p < .001). WHZ improved significantly at week 4 (mean difference = 0.08, 95% CI [0.01, 0.15], p = .022) and week 8 (mean difference = 0.29, 95% CI [0.18, 0.40], p < .001), whereas WAZ improved significantly only at week 8 (mean difference = 0.23, 95% CI [0.16, 0.31], p < .001). HAZ did not show a statistically significant change during follow-up. These findings suggest that locally based supplementary feeding was associated with short-term improvement in weight-related anthropometric outcomes, while improvement in linear growth was limited during the observation period. The high adherence observed in this study also supports the feasibility of delivering locally based supplementary feeding through routine community health services.